2001
DOI: 10.1128/cmr.14.4.872-908.2001
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunization in the United States: Developments over the Past Decade

Abstract: SUMMARY The Centers for Disease Control and Prevention has identified immunization as the most important public health advance of the 20th century. The purpose of this article is to review the changes that have taken place in active immunization in the United States over the past decade. Since 1990, new vaccines have become available to prevent five infectious diseases: varicella, rotavirus, hepatitis A, Lyme disease, and Japanese encephalitis virus infection. Improved vaccines have been deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 315 publications
(254 reference statements)
0
15
0
Order By: Relevance
“…Influenza virus infection remains a major health problem worldwide with annual epidemics, which are often complicated by significant morbidity and mortality despite the availability of rationalized vaccination protocols based on the use of inactivated virus (8,22,26). There are, however, two major drawbacks with this vaccine: firstly, the protection induced by the vaccine is short-lived and therefore requires annual administration, and secondly, the vaccine is only capable of eliciting a strain-specific antibody response (16,22,26).…”
mentioning
confidence: 99%
“…Influenza virus infection remains a major health problem worldwide with annual epidemics, which are often complicated by significant morbidity and mortality despite the availability of rationalized vaccination protocols based on the use of inactivated virus (8,22,26). There are, however, two major drawbacks with this vaccine: firstly, the protection induced by the vaccine is short-lived and therefore requires annual administration, and secondly, the vaccine is only capable of eliciting a strain-specific antibody response (16,22,26).…”
mentioning
confidence: 99%
“…This tetanus toxoid preparation is one of the most used antigenic proteins in human active vaccination protocols for preventing tetanus disease (Fig. 3C) with minimum toxic side-effects, 110 allowing the potential use of our morphine vaccine model for clinical trials.…”
Section: Immunologic Approaches For Opiate Dependencementioning
confidence: 99%
“…Research into the immunogenicity of HIB demonstrated increased antigenic properties and a more robust antibody response to its purified capsular polysaccharide, polyribosylribitol phosphate, when conjugated to a protein carrier (4). Placebo-controlled trials of the effectiveness of the immunologic response to the conjugated HIB vaccine in children showed nearly 100% protection of those vaccinated.…”
Section: Preventing Disease With Life-saving Immunizationsmentioning
confidence: 99%
“…Placebo-controlled trials of the effectiveness of the immunologic response to the conjugated HIB vaccine in children showed nearly 100% protection of those vaccinated. This led to the Food and Drug Administration (FDA) approval of the first HIB vaccines for a primary immunization series beginning at 2 mo of age (4). Pediatric clinicians translated research discoveries to practice.…”
Section: Preventing Disease With Life-saving Immunizationsmentioning
confidence: 99%
See 1 more Smart Citation